Current State of Platelet-rich Plasma in the Treatment of Rheumatic Disease: A Retrospective Review of the Literature - Jacobs, Adam; Elghawy, Omar; Lugo Baruqui, Diego; Aly Elghawy, Ahmed (Current Rheumatology Reviews, 2023)
Introduction: Rheumatic diseases are a spectrum of autoimmune or inflammatory diseases that cause damage to the musculoskeletal system as well as vital organs, such as the heart, lungs, kidneys, and central nervous system. Methods: The study of rheumatic disease has made great progress in the understanding and management of these conditions in the last few decades using disease-modifying antirheumatic drugs and synthesized biological immunomodulating therapies. However, one potential treatment that has not been well investigated in rheumatic disease is platelet-rich plasma (PRP). PRP is proposed to facilitate the healing of injured tendons and ligaments through a variety of mechanisms, including mitogenesis, angiogenesis and macrophage activation via cytokine release, although its exact mechanism is unclear. Result: There has been a great deal of work in determining the exact preparation method and composition of PRP for regenerative purposes in orthopedic surgery, sports medicine, dentistry, cardiac surgery, pediatric surgery, gynecology, urology, plastic surgery, ophthalmology, and dermatology. Despite this, there is a paucity of research on the impact of PRP on rheumatic disease. Conclusion: This study aims to summarize and evaluate the current research concerning the use of PRP in rheumatic disease.
Keywords: osteoarthritis